Tecnologías del aprendizaje y el conocimiento en el proceso de enseñanza-aprendizaje de la asignatura de Lengua y Literatura en el nivel de Bachillerato de la Unidad Educativa Adolfo Valarezo en el año lectivo 2023-2024. - Armijos Pereira, Jenny Rocio (2024)
Learning and Knowledge Technologies (TAC) are fundamental in the teaching-learning process student-centered, facilitating their active participation in knowledge construction. In this context, the teacher acts as a mediator and his or her role is to guide and enhance the meaningful learning of students in a digital environment in constant evolution through guidelines and methodologies that promote critical thinking, autonomy, and reflection. The present work on Curricular Integration analyzes the use of Learning and Knowledge Technologies by teachers in the teaching-learning process of the Language and Literature subject at the high school level in the Adolfo Valarezo Educational Unit in the academic year 2023-2024. For this, an exhaustive bibliographic review was carried out using various documents from repositories and academic search engines, to identify the characteristics of the TAC tools and their use by teachers for teaching the Language and Literature subject. The methodology employed is a quantitative approach of exploratory-descriptive type, the sample include the participation of 7 teachers, the instrument used for data collection was a structured questionnaire composed of Yes/No dichotomous questions and Likert scale questions; It is concluded that the TACs are used for teaching Language and Literature: online learning platforms, educational applications, and interactive content. It is also confirmed that teachers mostly use Learning and Knowledge Technologies in their tasks. Keywords: Learning Technologies, Teaching-Learning, Language-Literature.